THE ANALYSIS OF PREPOTIONAL PHRASE USAGE IN TAYLOR SWIFT’S SONG LYRICS - Tarihoran, Rezky Khoirina; Pratiwi, Rizky; Anggraini, Aisha Tri (PHILOLOGY Journal of English Language and Literature, 2024)
Prepositional phrase is a collection of words that includes a preposition, its object, and any words that alter the object. It is only part of a sentence and cannot stand alone as a complete notion. The research focuses on analyzing these prepositional phrases in Taylor Swift's song lyrics using Eggenscwiler theory. The authors employed a qualitative method, presenting the data in tabular form, and subsequently provided a detailed description of the identified data.. This study found that Taylor Swift uses a wide range of prepositions in her song lyrics, including common prepositions such as “in”, "on”, and "with", as well as less common prepositions such as "beneath", "behind", and "off".